Effect of surgical drilling on cochlear potentials - K. Preś; L. Pośpiech; M. Mazur; M. Kubacka; B. Rostkowska-Nadolska; W. Michalski (Archives of Acoustics, 2005)
The aim of the experiment was to examine the effect of noise and mechanical vibrations generated during the drilling of the bones surrounding the cochlea on the cochlear microphonics (CM). The experiment was carried out on a group of 40 guinea pigs divided equally into a group to be studied and a control group. In the studied group, CM values were measured three times: immediately after opening the bulla, after 30 minutes of nonstop drilling and two hours later, whereas in the control group they were measured twice: immediately after opening the bulla and 2.5 hours later. In this way the post-drilling shock and the long-term injuries to the cochlea could be studied. A statistical analysis of the obtained results shows that surgical drilling may cause an average decrease of 50-60% in CM values in comparison with the control group.